Development of Affective Attitude Instruments: Bibliometrics on the Scopus Database 2014 – 2023 - Suyono Suyono; Nuryani Dwi Astuti; Heri Retnawati; Syarief Fajaruddin; Ari Setiawan; Mohd Kasturi Nor Abd Aziz; Satrian Suhendar (FKIP Universitas Lampung, 2026)
This study aims to map publication trends, knowledge structures, and research gaps in the development of affective attitude instruments indexed in Scopus during 2014–2023. This study uses bibliometric analysis. A literature search was conducted in the Scopus database using the keywords